CLEC‐2 stimulates IGF‐1 secretion from podoplanin‐positive stromal cells and positively regulates erythropoiesis in mice. (20th April 2021) - Otake, Shimon; Sasaki, Tomoyuki; Shirai, Toshiaki; Tsukiji, Nagaharu; Tamura, Shogo; Takano, Katsuhiro; Ozaki, Yukio; Suzuki‐Inoue, Katsue
Abstract: Background: Erythropoiesis is a complex multistep process by which erythrocytes are produced. C‐type lectin‐like receptor 2 (CLEC‐2) is a podoplanin (PDPN) receptor almost exclusively expressed on the surface of platelets and megakaryocytes. Deletion of megakaryocyte/platelet CLEC‐2 was reported to cause anemia along with thrombocytopenia in mice. PDPN‐expressing stromal cells in the bone marrow (BM) were also reported to facilitate megakaryocyte expansion and maturation depending on the CLEC‐2/PDPN interaction. Objectives: We investigated how specific deletion of CLEC‐2 in megakaryocytes/platelets leads to anemia. Methods: We used flow cytometry to analyze maturation of erythroblasts, apoptotic cell death, and cell cycle distribution. CLEC‐2 stimulated PDPN‐expressing stromal cell–conditioned medium was analyzed by cytokine array and ELISA, and co‐cultured with immature erythroblasts. Cytokine levels in serum and BM extracellular fluid were quantified by ELISA. Results: We observed increased apoptosis of BM erythroblasts in megakaryocyte/platelet‐specific CLEC‐2 conditional knockout ( Clec1b ΔPLT ) mice. Moreover, PDPN‐expressing stromal cells in the BM secreted insulin‐like growth factor 1 (IGF‐1) depending on the CLEC‐2/PDPN interaction. Pretreatment with IGF‐1 receptor inhibitor increased apoptosis rate and decreased the proliferation of erythroblasts in vitro . Furthermore, in Clec1b ΔPLT mice, IGF‐1 concentrations in serum and BM extracellular fluid were decreased, and IGF‐1 replacement in Clec1b ΔPLT mice attenuated anemia. Conclusions: Our findings suggest that IGF‐1 secretion from PDPN‐expressing stromal cells by CLEC‐2 stimulation positively regulates erythroblasts. This novel mechanism of erythropoiesis regulation indicates that a microenvironment consisting of megakaryocytes and PDPN‐expressing stromal cells supports erythropoiesis.